Computer-aided design model parameterisation to derive knowledge useful for manufacturing design decisions. (March 2018) - Robinson, Trevor; Friel, Imelda; Armstrong, Cecil G; Murphy, Adrian; Butterfield, Joe; Price, Mark; Marzano, Adelaide
This article presents a number of novel approaches for deriving intelligence from the parameterisation of computer-aided design models to assist the engineer in making manufacturing-related decisions. During the design process, a disjoint can occur between the nominally defined computer-aided design feature parameters and the dimensions which govern manufacture and influence ease of product assembly. In this work, a link between the two representations is established, which simplifies the process of using the parameters defining the features in the computer-aided design model to make manufacturing-related decisions such as the allocation of dimensional tolerances or dealing with fit issues. It also offers insights about how the model should be parameterised to provide the optimal model utility from the designer's perspective with respect to the manufacturing domain.